Innovative Advances in Connectivity and Community Pharmacist Patient Care Services: Implications for Patient Safety. Issue 8 (13th July 2018) - Bacci, Jennifer L.; Berenbrok, Lucas A.
Abstract : The scope of community pharmacy practice has expanded beyond the provision of drug product to include the provision of patient care services. Likewise, the community pharmacist's approach to patient safety must also expand beyond prevention of errors during medication dispensing to include optimization of medications and prevention of adverse events throughout the entire medication use process. Connectivity to patient data and other health care providers has been a long‐standing challenge in community pharmacy with implications for the delivery and safety of patient care. We describe three innovative advances in connectivity in community pharmacy practice that enhance patient safety in the provision of community pharmacist patient care services across the entire medication use process. Specifically, we discuss the growing use of immunization information systems, quality improvement platforms, and health information exchanges in community pharmacy practice and their implications for patient safety.